2008
DOI: 10.1016/j.immuni.2008.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional Regulation of Il10 Gene Expression Allows Natural Killer Cells to Express Immunoregulatory Function

Abstract: Natural killer (NK) cells play a well-recognized role in early pathogen containment and in shaping acquired cell-mediated immunity. However, indirect evidence in humans and experimental models has suggested that NK cells also play negative regulatory roles during chronic disease. To formally test this hypothesis, we employed a well-defined experimental model of visceral leishmaniasis. Our data demonstrated that NKp46(+)CD49b(+)CD3(-) NK cells were recruited to the spleen and into hepatic granulomas, where they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
141
1
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(153 citation statements)
references
References 64 publications
(82 reference statements)
8
141
1
3
Order By: Relevance
“…It seems plausible that 3 regulatory mechanisms like transcriptional regulation, ARE mediated 3Ј UTR regulation, and hsa-miR-106a mediated 3Ј UTR regulation may critically regulate IL-10 expression. In fact, recently, it has been shown that inhibitory function of NKp46 ϩ CD49b ϩ CD3 Ϫ NK cells recruited in the hepatic granulomas in experimental model of visceral leishmaniasis was correlated with high IL-10 production as a result of increased stability of IL10 mRNA (28). It is very likely that hsa-miR-106a mediated posttranscriptional control could potentially be involved in fine tuning the critical level of IL-10 expression in a context-dependent manner, and hence dictates the outcome of immune response to specific external stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…It seems plausible that 3 regulatory mechanisms like transcriptional regulation, ARE mediated 3Ј UTR regulation, and hsa-miR-106a mediated 3Ј UTR regulation may critically regulate IL-10 expression. In fact, recently, it has been shown that inhibitory function of NKp46 ϩ CD49b ϩ CD3 Ϫ NK cells recruited in the hepatic granulomas in experimental model of visceral leishmaniasis was correlated with high IL-10 production as a result of increased stability of IL10 mRNA (28). It is very likely that hsa-miR-106a mediated posttranscriptional control could potentially be involved in fine tuning the critical level of IL-10 expression in a context-dependent manner, and hence dictates the outcome of immune response to specific external stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…A striking example of the difference between short-and long-term cultures is IL-10 expression. Whereas Il10 mRNA is rapidly induced in activated NK cells, IL-10 is not secreted until much later in an immune response (54).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that, at least in the steady state, the Il10-39 UTR mediates Il10 mRNA instability more profoundly in B cells than in macrophages and thus confers stronger suppression of IL-10 protein production in the former cell type. Recently, posttranscriptional regulation of Il10 gene expression has been shown to control specifically IL-10 secretion by NK cells (47). Furthermore, it has been shown that, compared with normal melanocytes, the melanoma cell line MNT1 exhibits reduced cytoplasmic levels of AU-rich element binding factor 1, an AU-rich element binding protein that mediate mRNA instability, resulting in IL-10 overexpression and tumor escape (40).…”
Section: Discussionmentioning
confidence: 99%